Tax Avoidance: Employment Benefits Liability, Sales Growth, Capital Intensity, Profit Management, And Inventory Intensity - Musyafa’ah Musyafa’ah; Nita Andriyani Budiman; Zamrud Mirah Delima (JAS (Jurnal Akuntansi Syariah), 2023)
This research analyzes the influence of employee benefit obligations, sales growth, capital intensity, earnings management, and inventory intensity on tax avoidance. The population in this study are primary consumer goods companies listed on the Indonesia Stock Exchange in 2017-2021. The sampling technique used purposive sampling so that 137 research samples were obtained. The data source comes from secondary data in company financial reports. The data analysis technique used is multiple linear regression analysis with the help of IBM SPSS 24 software. The results of this research show that earnings management positively affects tax avoidance. Inventory intensity negatively affects tax avoidance. Employee benefit obligations, sales growth, and capital intensity do not affect tax avoidance. This research can enrich agency and stakeholder theory by identifying the role of earnings management and inventory intensity in corporate tax strategies. Companies need to consider wise earnings management and evaluate inventory policies to optimize the reduction of tax liabilities while still complying with applicable tax regulations.